An assessment of the impact of participation in the Oceanographic Research Institute's Cooperative Fish Tagging Project on angler attitudes and behaviour. Issue 4 (2nd October 2022) - Mann-Lang, JB; Mann, BQ; Jordaan, GL; Daly, R
Abstract : Scientific output has proven the value of the Oceanographic Research Institute's Cooperative Fish Tagging Project (ORI-CFTP) to biological and fisheries research, with more than 95 published manuscripts based on data from the ORI-CFTP. This study reviews the project from the perspective of participating anglers. A total of 267 members of the ORI-CFTP responded to an online survey designed to gather data on the profile of tagging members, their preferred methods of communication, attitudes towards fish tagging and fish conservation in general, changes in angling behaviour since becoming a member of the project, and support for the continuation of the ORI-CFTP. The results reveal that the ORI-CFTP has indeed made a considerable contribution towards improving the conservation ethics and behaviour of marine recreational anglers in South Africa. Improved communication with anglers— both taggers and non-taggers—through the ORI-CFTP has the potential to amplify much-needed conservation information to the broader angling community and thereby enhance environmental awareness. Recommendations on how to improve the ORI-CFTP and other angling-related citizen science projects are provided.